Factors Influencing International Students’ Willingness to Seek Support in Canada - Le, Thu Thi Kim; Tran-Mai, Phuong Anh; Tran, Elena (Canadian Journal of Higher Education / Revue canadienne d'enseignement supérieur, 2025)
This study examines factors influencing international students’ help-seeking behaviour in Canada using the theory of planned behaviour (TPB) framework. Semi-structured interviews with 19 international students from diverse backgrounds were analyzed using thematic analysis. Findings revealed that students exhibited selective, cautious approaches whereby help-seeking preferences are domain-specific and relationally strategic, matching problems to appropriate support sources based on expertise, shared experience, and willingness to help. Our findings demonstrate how TPB operates differently in cross-cultural contexts where students navigate dual cultural frameworks, while also revealing how multiple intersecting identities compound to create unique help-seeking contexts beyond TPB’s dimensions. We introduce “strategic non-help-seeking” as a key conceptual contribution: a deliberate, rational, decision-making process whereby students actively choose not to engage with support systems based on careful evaluation of costs, benefits, and contextual constraints. Findings underscore the need for Canadian institutions to move beyond one-size-fits-all approaches and toward culturally responsive, accessible support systems recognizing international students’ diverse, intersecting needs.